11q24.2‐25 micro‐rearrangements in autism spectrum disorders: Relation to brain structures. (3rd September 2015) - Maruani, Anna; Huguet, Guillaume; Beggiato, Anita; ElMaleh, Monique; Toro, Roberto; Leblond, Claire S.; Mathieu, Alexandre; Amsellem, Frederique; Lemière, Nathalie; Verloes, Alain; Leboyer, Marion; Gillberg, Christopher; et al.
Abstract : Jacobsen syndrome (JS) is characterized by intellectual disability and higher risk for autism spectrum disorders (ASD). All patients with JS are carriers of contiguous de novo deletions of 11q24.2‐25, but the causative genes remain unknown. Within the critical interval, we hypothesized that haploinsufficiency of the neuronal cell adhesion molecule Neurotrimin (NTM) might increase the risk for ASD and could affect brain structure volumes. We searched for deleterious mutations affecting NTM in 1256 ASD patients and 1287 controls, using SNP arrays, and by direct sequencing of 250 ASD patients and 180 controls. We compared our results to those obtained from independent cohorts of ASD patients and controls. We identified two patients with Copy Number Variants (CNV) encompassing NTM, one with a large de novo deletion, and a clinical phenotype of JS (including macrocephaly), and a second with a paternally inherited duplication, not consistent with JS. Interestingly, no similar CNVs were observed in controls. We did not observe enrichment for deleterious NTM mutations in our cohort. We then explored if the macrocephaly in the patient with JS was associated with a homogeneous increase of brain structures volumes using automatic segmentation. Compared to subjects without NTM micro‐rearrangements (n=188), the patient had an increased volume of the sub‐cortical structures but a decrease of the occipital gray matter. Finally our explorations could not incriminate NTM as a susceptibility gene for ASD, but provides new information on the impact of the 11q24.2‐25 deletion on brain anatomy. © 2015 Wiley Periodicals, Inc.